Seasonal and interannual variability of the Weddell Polynya on the monthly average climatic data on sea ice closeness - Ju. V. Artamonov; A. A. Bukatov; V. N. Eremeyev; E. A. Skripaleva (Ukrainian Antarctic Journal, 2009)
On the base of data on sea ice closeness seasonal and interannual Weddell Polynia variability is analyzed. Values of sea ice closeness (in percent) in 1°x1° grid for the period 1969-2008 from data set of British Atmospheric Data Centre (BADC) HadISST ICE and NCEP Data are used. For Southern Ocean sector between 60°S and Antarctica coast and 10°W-10°E for each year monthly average summary areas with ice various closeness are calculated. Here occurrence of Weddell Polynia is most probable. It is shown, that in average annual climatic ice field different closeness Weddell Polynia is shown in decrease of 35-45 % ice closeness in area between 60-65°S and 0-20°E. In climatic seasonal cycle Weddell Polynia is observed in November-December as closed space of ice with closeness decrease by 20-30%. This space separated from open Ocean by the crosspiece of solid-ice. In this area the maximum of annual harmonic amplitude in seasonal variability of sea ice closeness is marked. Climatic seasonal scheme of Weddell Polynia forming undergoes significant interannual variability, which is connected with large-scale variability in the ocean-atmosphere system due to Antarctic Circumpolar Wave.